2010
DOI: 10.2478/s11772-010-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparing guided modal properties of surface waves along single- and double-negative indexed slab waveguides

Abstract: The guided dispersion characteristics of the fundamental symmetric and asymmetric modes of surface waves along single- and double-negative indexed slab waveguides are investigated, and a comparative analysis made when varying the single- and double-negative permittivity and permeability. While the values of the permittivity and permeability of the slab region are varied to obtain a salient picture of the guided dispersion characteristics, identical absolute product values are used for both slab cases to facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…It is interesting to note that the authors of [6][7][8][9][10][11][12] indicated that transverse TE m , TM m and surface modes can only propagate in the examined 1D and 2D isotropic and uniaxial anisotropic metamaterial waveguides. It means that the longitudinal components of EM waves are equal to zero.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting to note that the authors of [6][7][8][9][10][11][12] indicated that transverse TE m , TM m and surface modes can only propagate in the examined 1D and 2D isotropic and uniaxial anisotropic metamaterial waveguides. It means that the longitudinal components of EM waves are equal to zero.…”
Section: Introductionmentioning
confidence: 99%
“…The calculations were fulfilled for lossless materials. In [7], dispersion characteristics of the 1D slab waveguides of lossless DPS and DNG materials were investigated and compared. In the article, the T M m modes with m = 0, 1, 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many papers have reported the theoretical and experience development of metamaterials [12][13][14][15][16][17][18][19]. The variety of technologies for creation of engineering metamaterials increases rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…In our work the double negative (DN) metamaterial is defined by values s 1 = s 2 = s 3 = s 4 = −1; double positive (DP) material [13] is determined by values s 1 = s 2 = s 3 = s 4 = 1; single negative metamaterial (SN) is defined by values s 1 = s 2 = 1,…”
Section: Introductionmentioning
confidence: 99%